An Appraisal of Irrigation Water Resources of Nalanda District (Bihar) in Retrospect and Prospect - Sinha, B.P (Journal of Soil and Water Conservation, 2022)
Nalanda District (Bihar) receives about 1000 mm. of rainfall annually. More than 80 percent of it is received during rainy season of four months (July-Oct.). Previously the seasonal river system of the District had the net work of .Dynes (Channels) and Ahars (Reservior) to Store Water which protected the area from general failure of Crops by drought. With the abolition of Zamindari in 1950, these works have been left to degenerate and now greater part of water received during rainy season runs into Jala area and Mokamah tal of Patna District instead of percolating down to increase the ground water table. With the adoption of multiple crop farming, ground water is being exploited indiscriminately resulting in more withdrawal of underground water than recharge. To maintain the balance between withdrawal and recharge, it is essential to adopt various methods of recharging underground water.